WAYS TO ENSURE UNCONVENTIONAL EMPLOYMENT (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Unconventional employment has become a prominent feature of labor markets worldwide, including in Uzbekistan. This comprehensive analysis examines the various forms of non-standard employment arrangements in Uzbekistan, their economic and social implications, and strategies for ensuring sustainable development. The study explores self-employment, the informal sector, gig economy jobs, freelancing, and temporary or part-time work as prevalent forms of unconventional employment.